Equity Research on Pharmaceutical Sector - Jain, Naman (ATLAS SkillTech University, 2024)
The "Pharmaceutical Sector in India" project equips IIFL Securities with comprehensive insights into the industry's dynamics, fostering well-informed investment decisions and enhancing their financial services. This research aligns with their core activities, further solidifying their position as a leading financial institution. As the Indian pharmaceutical sector continues to play a pivotal role in global healthcare, this project's findings offer a roadmap for capitalizing on its potential for growth and innovation.
Project Report on Equity Research on Pharmaceutical Sector (2022-24) Under the Guidance of Prof. Sweta Kumari
Keywords: Pharmaceutical Sector; Pharmaceutical; IIFL Securities; Indian pharmaceutical sector; global healthcare